Agency, paratextuality, and queer pedagogy: analysing Javier Sáez del Álamo's translator's notes. - Villanueva-Jordán, Iván; Martínez-Carrasco, Robert (Perspectives: Studies in Translatology, 2023)
This study explores the use of paratexts as a means of translator's agency and queer pedagogy in the translations made by Javier Sáez del Álamo, a Spanish sociologist who has translated authors such as Judith Butler, Jack Halberstam, and Lee Edelman. Translator's notes are generally understood as a strategy which connects the target text to the reference framework provided by the source text. Yet, translator's notes also make up a textual or paratextual dimension with its own functions and effects regarding the core contents of the text. Translator's notes may have a considerable influence on the reception of a text, guiding the readers in representing alterity, promoting a particular understanding or reception of translation, or representing the values, ideas, and attitudes of the translator, be it explicitly or implicitly. This article analyses Sáez del Álamo's Spanish translations of three books by Jack Halberstam – Female Masculinity (1998), The Queer Art of Failure (2011) and Trans* (2018a) – and considers to what extent Saez del Álamo's notes become effective micro-political actions of queer pedagogy.